Research on Gearbox Fault Diagnosis based on Improved LMD Algorithm - Haibo Xing; Yue Chen; Jinghao Li (Jixie chuandong)
Gearbox is one of the most critical and fault-prone components in a mechanical transmission system. Aiming at the fault diagnosis of gearbox，an Improved Local Mean Decomposition （ILMD） algorithm is proposed and applied to the extraction of fault features of gearbox. Firstly，in order to reduce the modal aliasing problem of the Local Mean Decomposition （LMD） algorithm，an optimized rational spline interpolation algorithm is introduced to the construction of the envelope curve. Then，the ILMD algorithm is used to decompose the measured vibration signal into a series of product functions （PF）. After that，the effective component which contains the most fault information among the decomposition results is selected based on the kurtosis. Finally，through the analysis of the envelope spectrum of the effective component，the diagnosis of gearbox fault is realized. The experimental results demonstrate that the proposed method can effectively suppress the mode mixing，and identify the gear wear failure precisely.